"Zip me up, and cool me down": Molar narratives and molecular intensities in 'helicopter' mental health services. (March 2016) - McGrath, Laura; Reavey, Paula
Abstract: Experiences of the space–time dimensions of contemporary mental health services are shaped according to what we describe here as a 'helicopter service', where professionals drop down into service users' lives for short, often pre-determined bursts of time. This can create a system where users' experiences are observed and assessed from a more distanced and circumscribed perspective. This paper considers the implications of these systemic changes, using interviews with current UK service users. To help in the exploration of the complexities faced by service users', we useDeleuze and Guatarri's (1987) distinction between molar and molecular forms of organisation. A process oriented thematic analysis discusses: a) Affording narratives of distress: Molarity, monitoring and space in service interactions and b) Narratives in therapy: Compartmentalising the distressed self. Multiple aspects of the relationship between space and distress are explored. An understanding of experiences of distress beyond the boundaries of the molar, which considers its intensive, molecular and transformative nature, may help to open up engagement with the affective and emotional dimensions of mental health.